Nilai-Nilai Edukatif Qur’an Surah Al-Israa’ Ayat 23-24 Tentang Akhlak Kepada Orangtua Dan Implikasinya Terhadap Karakter Religius Siswa - Sulaiman, Husnan; Saepulloh, Aceng (STAI Al-Musaddadiyah Garut, 2024)
Surah Al-Israa’ verses 23-24 serve as a crucial source of educational ideas and concepts for Muslim families. These verses provide foundational guidance on educating children to avoid associating partners with Allah and to show devotion to their parents, aligning with the values prescribed in Islamic law. This study aims to: (1) Understand the definition and significance of Islamic education, (2) Identify the educational values in Surah Al-Israa' verses 23-24 regarding children's conduct towards their parents, and (3) Explore how these values influence the development of students' religious character from the perspective of Islamic education. This research employs a library research methodology, using a content analysis approach. Data sources include primary and secondary materials, gathered through documentation methods involving reading, reviewing, and analyzing Quranic exegesis, Hadith collections, and relevant books. The content analysis method is applied to interpret the meanings embedded in the Quranic text. Subsequent to this interpretation, an in-depth analysis is conducted to address the research questions. The findings reveal that the educational values embedded in Surah Al-Israa' verses 23-24 concerning filial piety include showing kindness to parents, speaking to them with respect, and praying for them. The implications for the development of students' religious character, particularly in the context of 'birrul walidain' (benevolence towards parents), indicate an enhancement in students' behavior towards their parents. This includes increased acts of kindness, patience in caring for parents, avoiding actions that harm parents, demonstrating respect and humility towards them, and praying for their well-being both during their lives and after their death. Keywords: Islamic Education, Quran, Religious Character